Functional magnetic resonance brain imaging of imagined walking to study locomotor function after stroke. Issue 1 (January 2021) - Boyne, Pierce; Doren, Sarah; Scholl, Victoria; Staggs, Emily; Whitesel, Dustyn; Maloney, Thomas; Awosika, Oluwole; Kissela, Brett; Dunning, Kari; Vannest, Jennifer
Highlights: Imagined walking evokes greater overall brain activation in stroke survivors vs. controls, likely revealing compensatory changes. Greater activation during imagined walking is associated with worse gait function, raising the possibility of maladaptation. Compared with unilateral knee extension, imagined walking shows reverse associations with stroke and gait function. Abstract: Objective: Imagined walking has yielded insights into normal locomotor control and could improve understanding of neurologic gait dysfunction. This study evaluated brain activation during imagined walking in chronic stroke. Methods: Ten persons with stroke and 10 matched controls completed a walking test battery and a magnetic resonance imaging session including imagined walking and knee extension tasks. Brain activations were compared between tasks and groups. Associations between activations and composite gait score were also calculated, while controlling for lesion load. Results: Stroke and worse gait score were each associated with lesser overall brain activation during knee extension but greater overall activation during imagined walking. During imagined walking, the stroke group significantly activated the primary motor cortex lower limb region and cerebellar locomotor region. Better walking function was associated with less activation of these regions and greater activation of medial superior frontal gyrus area 9. Conclusions: Compared with knee extension, imagined walking was less sensitive to stroke-related deficits in brain activation but better at revealing compensatory changes, some of which could be maladaptive. Significance: The identified associations for imagined walking suggest potential neural mechanisms of locomotor adaptation after stroke, which could be useful for future intervention development and prognostication.